Expression Characteristics of SODD and ALG-2 as Possible Biomarkers for Evaluating Lymphatic Metastasis Potential of Hepatocarcinoma in a Mouse Model - Wang, Shaoqing; Gao, Feng; Sun, Yurong; Yu, Xiuwen; Bai, Qingyang; Tang, Jianwu; Wang, Xianyan (Cellular and Molecular Biology, 2022)
Annexin A7 has been confirmed in our previous research to be an important factor in lymph node metastasis (LNM) of hepatocellular carcinoma (HCC). SODD and ALG-2 are the binding proteins of Annexin A7 and can work in protein complexes. The present study was carried out with the constructed cell lines in mouse model of metastasis for further elaboration of possible mechanisms and identification of associated genes in the LNM of HCC. This experiment used inbred Chinese 615 mice, as well as Hca-F and Hca-P cells. Quantification of the relative messenger RNA (mRNA) expression of SODD and ALG-2 was realized by using qRT-PCR. Quantification of the protein expressions of SODD and ALG-2 was achieved by using western blot. Experimental mice (n=160) (6-8weeks old, 18-22g, SCXK [LIAO] 2008-0002) were randomly classified into four groups equally, which were separately inoculated with Hca-F, Hca-P, FAnxa7-upregulated, and PAnxa7-upregulated cells. Serum levels of SODD and ALG-2 were measured by ELISA. Immunohistochemical analysis of SODD and ALG-2 was further conducted. Tumor LNM-related factors of SODD and ALG-2 showed the same tendency in their expression correspondingly with the up-regulated expression of Annexin A7. Our experiment further explored the roles of SODD and ALG-2 based on Annexin A7 up-regulation vectors construction and the establishment of corresponding controls in vivo. Furthermore, the mouse model of primary tumors was constructed by injecting Hca-F, FAnxa7-upregulated and Hca-P, PAnxa7-upregulated cells into the mouse footpad. Mice were sacrificed at the designated time points for detecting SODD and ALG-2 expression in tumor tissue and serum samples. Collectively, our work indicates SODD in tumors and in serum and ALG-2 in serum are valuable in evaluating LNM in mice with HCC.